Use of the Chinese version modified checklist for autism in toddlers in a high-risk sample in Taiwan. (May 2018) - Wong, Yi Shan; Yang, Ching-Chi; Stewart, Lydia; Chiang, Chung-Hsin; Wu, Chin-Chin; Iao, Lai-Sang
Highlights: Previous studies have found an urbanization disparity in the distribution of ASD diagnosis. The utility of Modified Checklist for Autism in Toddlers (M-CHAT) is well-studied in English-speaking populations and has been translated into different language versions. Until now, the M-CHAT has not been studied for validity of screening high-risk preschool children with ASD in Taiwan. In this study, Chinese Version Modified Checklist for Autism in Toddlers (C-M-CHAT) was used to detect high-risk preschool children with ASD in a rural and agricultural area of Taiwan. The preliminary results showed that utility of C-M-CHAT in a high-risk sample in a rural area of Taiwan is promising. Abstract: This study examined the utility of the Chinese version Modified Checklist for Autism in Toddlers (C-M-CHAT) in a high-risk sample. This study recruited 236 children aged from 18 to 47 months old in rural area of Southern Taiwan, including 113 children with Autism Spectrum Disorder (ASD) and 123 children with Developmental Delay (DD). Using failing any four of the 23 C-M-CHAT items as cutoff, it showed a sensitivity of 77.0% and a specificity of 72.4%. The positive predictive value (PPV) was 71.9% while the negative predictive value (NPV) was 77.4%. Using failing any three of the 14 new critical items–referred to as the "Brief 14"–as cutoff, it yielded a sensitivity of 70.8% and a specificity of 82.1%. The PPV of the "Brief 14" was 78.4% while the NPV was 75.4%. The preliminary results of the C-M-CHAT and the "Brief 14" performance demonstrated an acceptable predictive validity and promising utility for use in high-risk, rural populations in Taiwan.